Responsabilidad social municipal y la calidad de los servicios públicos en la provincia de Requena 2024 - Torrejon Hoyos, Ilich (2025)
The purpose of this final report was to determine the relationship between municipal social responsibility and the quality of public services in the Province of Requena, 2024. Where a basic, correlational study was carried out with a non-experimental design. A sample of 382 inhabitants was taken, and a questionnaire was used to collect information and data. The results obtained show that municipal social responsibility is rated as regular (25%), because it occasionally organizes and promotes cultural activities and supports entrepreneurs, lacks initiatives to encourage citizen participation in local economic matters and almost never implements an effective plan for solid waste management. Regarding the quality of public services, 24% of citizens rate it as regular, since sometimes the availability and quality of the electricity supply is adequate and local markets offer acceptable products in a clean environment, customer service in government offices is never excellent or effective in solving needs. Finally, a correlation coefficient of 0.686 was determined, indicating a moderate positive relationship between municipal social responsibility and the quality of public services.